Epidemiological and diagnostic aspects of spontaneous miscarriage in the department of gynecology-obstetric of the university hospital of Treichville in Abidjan - Yao, Ignace N.; Dia, Jean Marc L.; Menin, Michelle M.; Oyelade, Mouhedeen A.; Saki, Corneille T.; Okon, Gerard (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Describe the epidemiological and diagnostic of spontaneous aspects of early miscarriage in the department of the Gynecology Obsteric of Treichville University Teaching Hospital of Treichville in Abidjan. Methods: A cross-sectional study was performed from January 2016 to March 2017 on patients received for an early miscarriage (gestational age less than 14 weeks of amenorrhea). Results: We recorded 337 cases of miscarriage and it shows that miscarriage was frequently estimated at 58 percent. Our patients had a average age of 32.9 years, 60.4 percent of them with primary education and 48 percent are housewives. The patients were paucigestes in 46 percent and the majority of them were nulliparous (62 percent). 6 percent with history of high blood pressure; diabetes (3 percent) and 31 percent of patients were HIV positive. Patients had pelvic pain at the admission in (55 percent). A miscarriage appears before 10 weeks of amenorrhea (76.1 percent) of cases. Ultrasound showed ovular debris (47 percent) of patients and (55.4 percent) were chromosomal abnormalities on anatomy-pathological examination. Conclusions: Spontaneous abortions are common and pathological examination is essential for diagnosis.